(untitled) - Wisely, David (New York, 2009)
IP for 4G examines the concept of 4G, providing an in-depth background to the key technologies and developments shaping the new generation of mobile services, including Wireless Local Area Networks (WLANs), Worldwide Interoperability for Microwave Access (WiMAX), IP developments (SIP and Media Independent Handover), Internet Multimedia Subsystem (IMS), and 3G (HSDPA and LTE). The book addresses these key technological drivers in light of commercial propositions such as generating extra revenue and reducing costs, and offers an up-to-date briefing on the future of mobile communications in the coming years.
Keywords: Wireless Internet,Global system for mobile communications,Mobile communication systems